دراسة توصيفية لعينات من الزيوليت السوري (Latakia University Journal -Basic Sciences Series, 2018)
أجريت الدراسة على أربع عينات من الزيوليت الطبيعي ، والتي حصلنا عليها عن طريق المؤسسة العامة للجيولوجيا بدمشق، وهي تحمل الأرقام TS-18, TS-14, TS-9, TS-7 وهي مأخوذة من الطبقة البيروكلاستية الممتدة بين منطقة السيس وتلال مكحيلات. تمت دراسة العينات باستخدام تقنية انعراج الأشعة السينية X.R.D، تبين أن العينات تحتوي على الزيوليت الطبيعي الأنالسيم بنسب مختلفة بالإضافة إلى بعض الفلزات الأخـرى كالغضار والفلدسبار وأن العينة TS-14 تحتوي على نسبة عالية من الكالسيت. واستخدمت تقنية التحليل الحراري التفاضلي DTA وتبين أن البنية البلورية للزيوليت تنخرب حوالي الدرجة 830 0C، وأن الكالسيت يتفكك حوالي الدرجة 760 0C، وأن العينات تفقد جزيئات الماء الموجودة فيها بشكل تدريجي. تم تحديد السطح النوعي للعينات، وتبين أن العينات تمتلك سطحا نوعيا يتراوح ما بين (66 -100) m2 / g  كما أجري التحليل الكيميائي لتحديد تركيب العينات.We have studied four samples of natural zeolite obtained from G.G.E. in Damascus. These samples were taken from the extended area between Sees & M. Mountain. We studied these samples by different techniques such as X-Rays Diffraction which showed that these samples contain ANALSIM natural Zeolite range between 30-40% beside other components (Clay and Feldspar). The sample TS-14 contains Calcite with high ratio compared with the other samples. We also used the Differential Thermal Analysis, which showed that the crystalline structure of Zeolite gets destroyed at 830C0 and the calcite decomposes at 760C0. The samples will gradually lose water molecules at around 200C0. The adsorption of Nitrogen gas at 77K was also studied to determine the specific surface area of the samples, which ranged from 66 to100 square meter per gram. Chemical analysis was performed to determine the chemical structure of the samples.